Pengaruh Harga dan Promosi Terhadap Keputusan Pembelian Alat-Alat Komputer pada PT Sumber Utama Nusantara - Ahmad Fadli; Manda Dwipayani Bhastary; Ayu Kartika (Journal Of Business, Finance, and Economics (JBFE), 2022)
This study aims to determine the effect of training and organizational culture on employee career development at PT Sumber Utama Nusantara. The population of this study were 100 employees and a sample of 30 people using simple random sampling technique. The data collection technique used was through a questionnaire which measured using a Likert scale and processed statistically using multiple regression analysis and hypothesis testing t test. f test, and the determinant coefficient. From the data analysis of each variable, the multiple regression equation Y = Y = 5,395 + 103 X1 + - 239 X2 + e is obtained. Obtained Adjusted R Square value of 0.401, which means that X1 and X2 explain the effect on variable Y by 40.1% while the rest is explained by other variables outside the research. The t-value of the price variable (X1) is 991 and significant at .330. The hypothesis H0 is accepted and Ha is rejected. Therefore tcount 0.05, so it can be concluded that the price variable (X1) has a significant effect on purchasing decisions.